Ghost circles /. 7 - Smith, Jeff, 1960- (Bone, 2008)
The war in the valley rages on while the Bones, Gran'ma Ben, and their loyal rat creature cub venture on a dangerous trek to Atheia, the old city of the royal family. The goal is to bring Thorn to safety, but to do so they must first travel through fields of the mysterious ghost circles where reality meets the supernatural -- and all this while fending off deadly attacks from Briar, Kingdok, and the rat creatures.